SASTRA DALAM PERSPEKTIF PENDIDIKAN: KAJIAN PENGERTIAN, JENIS, DAN BENTUK APRESIASI - Rosmanila Lubis; Erna Ikawati (STKIP Subang, 2025)
This article examines literature from an educational perspective, focusing on three main aspects: the definition of literature, its various types, and forms of literary appreciation. This study is based on theoretical analysis derived from both classical literature and recent research. The results of the discussion indicate that literature is an expression of human experience expressed through aesthetic, imaginative, and meaningful language. Literary types can be classified based on form (prose, poetry, drama) and content (narrative, lyric, didactic, dramatic, and reflective). Each type has its own characteristics that reflect the diversity of culture and societal values.Furthermore, literary appreciation is understood as an active process involving the understanding, evaluation, and appreciation of literary works, encompassing not only cognitive aspects but also affective and social aspects. In an educational context, literary appreciation plays a crucial role in developing language skills, enriching vocabulary, fostering aesthetic sensitivity, and instilling moral and social values. These findings emphasize that literature learning in elementary schools should emphasize not only theory but also concrete experiences through reading, writing, discussion, and performance. Thus, literature not only functions as entertainment but also as an educational tool that supports the intellectual, emotional, and character development of students.